Patches

A hydrogel patch with a controlled ion ratio and carboxymethylcellulose improves shape retention, adhesive strength, and refreshing sensation, addressing back-staining issues.

JP7608812B2Active Publication Date: 2025-01-07LION CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020206094
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-11
Publication Date
2025-01-07
Estimated Expiration
2040-12-11

AI Technical Summary

Technical Problem

Existing patches containing hydrogels face issues with shape retention and back-staining, particularly when moisture content is high, and lack adhesive strength and a refreshing feeling.

Method used

A patch comprising a hydrogel crosslinked with a specific molar ratio of magnesium ions to aluminum ions, combined with carboxymethylcellulose, to enhance shape retention, adhesive strength, and provide a refreshing sensation.

Benefits of technology

The patch achieves compatibility with shape retention, prevents back-staining, and provides strong adhesion while offering a refreshing feel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608812000001
    Figure 0007608812000001
  • Figure 0007608812000002
    Figure 0007608812000002
Patent Text Reader

Abstract

To provide a patch containing a hydrous gel that has shape retentivity and is also less prone to back-staining, and further has adhesive force and a refreshing feel.SOLUTION: A patch contains a hydrous gel and a support. The hydrous gel contains (A) at least one selected from polyacrylic acid and a salt thereof and (B) a hydrous gel crosslinked with a crosslinker. In the crosslinker, the molar ratio between magnesium ions and aluminum ions (magnesium ions / aluminum ions) is 1.9 or more and less than 3.0.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a patch having a hydrogel. [Background technology]

[0002] A patch having a hydrogel has a three-dimensional structure and retains water by crosslinking one or more water-soluble polymers having at least one of a carboxyl group, a hydroxyl group, and an acetate group with a crosslinking agent. However, when the water content increases, the shape retention is lost, and the hydrogel may ooze out to the back side of the support during storage of the patch. For these reasons, a patch having a hydrogel that has both shape retention and suppression of back staining has been desired. In addition, a patch having both adhesive strength and a refreshing feeling has been desired. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-265373 [Patent Document 2] JP 2004-231567 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made in consideration of the above circumstances, and has an object to provide a patch containing a hydrogel that has both shape retention and inhibition of back staining, and has adhesive strength and a refreshing feel. [Means for solving the problem]

[0005] As a result of extensive research into achieving the above-mentioned object, the inventors have found that, although crosslinking with trivalent aluminum ions has conventionally been most commonly used, by using a specific molar ratio of divalent magnesium ions and trivalent aluminum ions, it is possible to obtain a patch having a hydrogel that has both adhesive strength and a refreshing feel, while also achieving good shape retention and inhibition of back staining, and have thus completed the present invention.

[0006] Therefore, the present invention provides the following patch. 1. A patch comprising a hydrogel and a support, The hydrogel is A patch comprising (A) one or more types of polyacrylic acid and its salts crosslinked with (B) a hydrogel crosslinked with a crosslinking agent, wherein the molar ratio of magnesium ions to aluminum ions (magnesium ions / aluminum ions) in the crosslinking agent is 1.9 or more and less than 3.0. 2. The patch according to 1, further comprising (C) one or more members selected from carboxymethylcellulose and its salts. 3. The patch according to 1 or 2, wherein the support is a knitted fabric. Effect of the Invention

[0007] According to the present invention, it is possible to provide a patch having a hydrogel that has both shape retention and inhibition of back staining, and has adhesive strength and a refreshing feel. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will be described in detail below. I. Hydrogel The hydrogel of the present invention is The composition contains a hydrogel in which (A) one or more types selected from polyacrylic acid and salts thereof are crosslinked with (B) a crosslinking agent, and the molar ratio of magnesium ions to aluminum ions (magnesium ions / aluminum ions) in the crosslinking agent is 1.9 or more and less than 3.0.

[0009] [Component (A)] The component (A) of the present invention is a water-soluble polymer having one or more groups selected from a carboxyl group, a hydroxyl group, and an acetate group, and may be used alone or in combination of two or more. Examples of the component (A) include polyacrylic acid and polyacrylic acid salts.

[0010] The polyacrylic acid salt may be one in which 20 to 80 mol % of the carboxyl groups in one polymer chain are neutralized. Examples of the salt include monovalent metal salts of polyacrylic acid such as sodium polyacrylate and potassium polyacrylate, amine salts of polyacrylic acid such as monoethanolamine polyacrylate, diethanolamine polyacrylate and triethanolamine polyacrylate, and ammonium salts of polyacrylic acid.

[0011] As the component (A), a commercially available product can be used, for example, the following product. Carboxyvinyl polymer: Carbopol (product name: manufactured by Goodrich Chemicals, USA) Polyacrylic acid: Toa Gosei Co., Ltd., "Jurimer AC-10H", weight average molecular weight: 150,000, neutralization degree: 0 mol% Polyacrylic acid: Toa Gosei Co., Ltd., "Jurimer SH8", weight average molecular weight: 1 million, neutralization degree: 0 mol% Polyacrylic acid: Toagosei Co., Ltd., "Jurimer AC-10P", weight average molecular weight: 9000, neutralization degree: 0 mol% Polyacrylic acid: Nippon Shokubai Co., Ltd. "AS-58", weight average molecular weight: 800,000, neutralization degree: 0 mol% Partially neutralized polyacrylic acid: "Aronvis AH-106X" manufactured by Toa Gosei Co., Ltd., weight average molecular weight: 4.5 million, neutralization degree: 40 mol% Partially neutralized polyacrylic acid: Showa Denko K.K., "Viscomate NP-800", weight average molecular weight: 5 million, neutralization degree: 35 mol% Partially neutralized polyacrylic acid: "Akupana AP-40F" manufactured by Sumitomo Seika Chemicals Co., Ltd., weight average molecular weight: 5 million, neutralization degree: 40 mol% Sodium polyacrylate: "Aronvis SX" manufactured by Toagosei Co., Ltd., weight average molecular weight: 4.5 million, neutralization degree: 100 mol% Sodium polyacrylate: Nippon Shokubai Co., Ltd. "FHS", weight average molecular weight: 4 million, neutralization degree: 100 mol%

[0012] As the component (A), polyacrylic acid or sodium polyacrylate having a weight average molecular weight of 10,000 to 10 million is preferred, and a combination of two or more of polyacrylic acid and its salts having a weight average molecular weight of 10,000 or more and less than 500,000, 500,000 or more and less than 2 million, or 2 million to 7 million is preferred. The weight average molecular weight means the weight average molecular weight measured by gel permeation chromatography (GPC) (polyacrylic acid equivalent).

[0013] The content of the component (A) in the gel composition is preferably 1 to 15% by mass, and more preferably 5 to 12% by mass, from the viewpoints of shape retention and adhesive strength.

[0014] [(B) Component] The component (B) of the present invention is a crosslinking agent, and can be used alone or in combination of two or more. Among them, those that release magnesium ions and aluminum ions in an aqueous solution are preferred. Specifically, any aluminum compound and magnesium compound can be suitably used. For example, alums such as potassium alum, ammonium alum, and iron alum, aluminum hydroxide, aluminum sulfate, aluminum chloride, aluminum glycinate, aluminum acetate, aluminum oxide, aluminum silicate, aluminum metasilicate, magnesium hydroxide, magnesium carbonate, magnesium sulfate, magnesium acetate, magnesium silicate, magnesium oxide, magnesium alumina hydroxide, magnesium aluminometasilicate, magnesium aluminosilicate, synthetic hydrotalcite, water-soluble compounds such as double salts containing these metals, poorly water-soluble compounds, and antacids containing aluminum and magnesium can be mentioned. Among them, potassium alum, aluminum hydroxide, aluminum glycinate, magnesium hydroxide, magnesium alumina hydroxide, magnesium aluminometasilicate, magnesium aluminosilicate, and synthetic hydrotalcite are preferred, and aluminum glycinate and synthetic hydrotalcite are more preferred. Commercially available products that can be used include dihydroxyaluminum aminoacetate: "Glycinal" manufactured by Kyowa Chemical Industry Co., Ltd., synthetic hydrotalcite: "Alcamac SH" manufactured by Kyowa Chemical Industry Co., Ltd., magnesium alumina hydroxide: "Sanarumin" manufactured by Kyowa Chemical Industry Co., Ltd., and magnesium aluminometasilicate: "Neusilin" manufactured by Fuji Chemical Industry Co., Ltd.

[0015] The molar ratio of magnesium ions to aluminum ions (magnesium ions / aluminum ions) in the crosslinking agent is 1.9 or more and less than 3.0, preferably 2.0 to 2.5. The ion ratio in the crosslinking agent is adjusted by the molar ratio in each crosslinking agent to be blended.

[0016] The hydrogel of the present invention is a hydrogel obtained by crosslinking the above-mentioned (A) component with the (B) crosslinking agent, and further includes other polymer compounds, such as (C) carboxymethylcellulose and its salts.

[0017] The degree of etherification of sodium carboxymethylcellulose is preferably 0.5 or more. The viscosity of a 1% by mass aqueous solution at 25°C is preferably 100 to 4,000 mPa·s, more preferably 1,500 to 3,000 mPa·s. The more linear the relationship between the concentration of the aqueous solution of carboxymethylcellulose and the viscosity, the more uniform the substituent distribution is, but in order to increase the effect, it is preferable to use one that is non-uniform. The ratio of the viscosity of a 5% by mass aqueous solution at 25°C to the viscosity of a 1% by mass aqueous solution at 25°C is preferably 400 to 3,000, more preferably 450 to 2,000. For example, sodium carboxymethylcellulose: CMC1380 (Daicel FineChem Co., Ltd.), CMC1390 (same as above), and CMC2280 (same as above) can be used. The above viscosity is a value measured using a BH type viscometer (rotor: No. 2, rotation speed: 20 rpm) manufactured by Tokyo Keiki Co., Ltd.

[0018] The content of component (C) in the gel composition is preferably 1% by mass or more from the viewpoint of suppressing backstaining, and is preferably 8% by mass or less, more preferably 2.5 to 5.5% by mass from the viewpoint of adhesive strength.

[0019] The water content in the hydrogel composition is preferably 65 to 80% by mass, more preferably 69 to 75% by mass.

[0020] The hydrogel of the present invention may contain appropriate amounts of the above-mentioned components, either alone or in combination, within the scope of the invention, such as surfactants, fillers, cellulose derivatives other than component (C), water-soluble polymeric compounds other than components (A) and (C), highly water-absorbent polymeric compounds other than component (A), polyhydric alcohols, oils, moisturizers, antioxidants, ultraviolet absorbing / scattering agents, preservatives, fragrances, etc.

[0021] As the surfactant, a nonionic surfactant, an anionic surfactant, a cationic surfactant, or an amphoteric surfactant can be used, and these can be used alone or in appropriate combination of two or more. When a surfactant is added, the amount thereof is about 0 to 5% by mass in the hydrogel.

[0022] Specific examples of the nonionic surfactant include polyglycerol fatty acid esters (having fatty acid residues and alkyl groups with 8 to 22 carbon atoms, preferably 10 to 18 carbon atoms) (e.g., diglycerol monostearate, etc.), polyoxyethylene glycerol fatty acid esters (e.g., polyoxyethylene glyceryl (POE10) monooleate, etc.), polyoxyethylene fatty acid esters, polyoxyalkylene alkyl ethers (e.g., polyoxyethylene alkyl ethers, polyoxypropylene alkyl ethers, polyoxyethylene polyoxypropylene alkyl ethers, etc.), polyoxyethylene alkyl phenyl ethers, polyhydric alcohol fatty acid partial esters (e.g., Examples of the fatty acid ester include glycerin fatty acid esters, propylene glycol fatty acid esters, sorbitan fatty acid esters, etc.), polyoxyethylene polyhydric alcohol fatty acid partial esters (for example, polyoxyethylene glycerin fatty acid esters, polyoxyethylene propylene glycol fatty acid esters, polyoxyethylene sorbitan fatty acid esters, etc.), polyoxyethylene castor oil, polyglycerin fatty acid esters, polyoxyethylene polyoxypropylene glycol, polyoxyethylene alkylphenyl ethers, fatty acid diethanolamides, polyoxyethylene alkylamines, ethanolamine fatty acid partial esters, alkylamine oxides, etc.

[0023] Among these nonionic surfactants, POE (25) lauryl ether, sucrose fatty acid ester, sorbitan monooleate, sorbitan monolaurate, sorbitan coconut oil fatty acid, sorbitan monostearate, glyceryl monooleate, glyceryl laurate, glyceryl coconut oil fatty acid, polyethylene glycol monolaurate, polyethylene glycol monooleate, glyceryl myristate, decaglyceryl monooleate, diglyceryl dioleate, hexaglyceryl monolaurate, propylene glycol monostearate, POE (20) sorbitan monooleate (polysorbate 80), POE (60) sorbitol tetraoleate, POE (40) monostearate, POE (10) oleyl ether, POE (10) nonylphenyl ether, POE (50) hydrogenated castor oil, POE (5) oleic acid amide, oleic acid diethanolamide, lauric acid diethanolamide, and the like are more preferred. In the above notation, for example, "POE(25)" indicates a structure in which 25 moles of ethylene oxide have been added.

[0024] The most preferred nonionic surfactants are polyoxyethylene alkyl ethers having an alkyl group of 12 to 18 carbon atoms, polyoxyethylene sorbitan fatty acid esters, and polyoxyethylene hydrogenated castor oil.

[0025] Examples of the anionic surfactant include higher fatty acid salts, alkyl ether carboxylates, polyoxyethylene alkyl ether carboxylates, alkyl sulfates, polyoxyethylene alkyl sulfates, alkyl isocyanates, alkylbenzene sulfonates, alkyl phosphates, and polyoxyethylene alkyl phosphates. As these salts, sodium salts, potassium salts, organic amine salts, and the like are preferred, and those in which the alkyl or alkenyl group has 8 to 22 carbon atoms, particularly 10 to 18 carbon atoms, are more preferred.

[0026] Among these, sodium oleate, sodium laurate, sodium myristate, sodium cetyl sulfate, sodium cetostearyl sulfate, sodium oleyl sulfate, sodium polyoxyethylene lauryl ether sulfate, sodium lauryl sulfate, dioctyl sodium sulfosuccinate sulfate, sodium coconut oil fatty acid hydrolyzed collagen, sodium glycyrrhizinate, sodium glycyrrhetinate, sodium triPOE(10) alkyl ether phosphate and their potassium salts, diethanolamine salts, triethanolamine salts, sodium N-acylmethyltaurine, and the like are more preferred.

[0027] Specific examples of the cationic surfactant include primary to tertiary fatty amine salts, quaternary ammonium salts, urea condensate salts of polyethylene polyamine fatty amides, and quaternary ammonium salts of urea condensates of polyethylene polyamine fatty amides. More specific examples include stearyl trimethyl ammonium chloride, lauryl trimethyl ammonium chloride, stearyl trimethyl ammonium saccharin, lauryl trimethyl ammonium saccharin, benzalkonium chloride, lauryl pyridinium chloride, cetyl pyridinium chloride, lauryl pyridinium chloride, and alkyl diaminoethyl glycine hydrochloride.

[0028] Specific examples of amphoteric surfactants include amino acids, sulfoamino acids, quaternary betaines, sulfobetaines, imidazolinium betaines, and the like. More specific examples of amphoteric surfactants include lauryl dimethylaminoacetic acid betaine, coconut oil alkyl betaines, coconut oil fatty acid amidopropyl betaines, coconut oil fatty acid hydrolyzed collagen, diethyl sebacate, and lecithin.

[0029] Examples of the filler include kaolin, bentonite, montmorillonite, smectite, zinc oxide, titanium oxide, silicic anhydride, etc. When a filler is added, the amount thereof is about 0 to 10% by mass in the hydrous gel.

[0030] Examples of cellulose derivatives other than component (C) include hydroxypropyl cellulose, hydroxyethyl cellulose, methyl cellulose, and salts thereof.

[0031] Examples of water-soluble polymeric compounds other than the above components (A) and (C) include gelatin, polyvinyl alcohol, polyvinylpyrrolidone, polyethylene oxide, sodium alginate, xanthan gum, gum arabic, gum tragacanth, karaya gum, and maleic anhydride copolymers.

[0032] As the highly absorbent polymeric compound other than the component (A), a non-water-soluble nonionic highly absorbent polymeric compound is preferable. Since the water-insoluble nonionic highly absorbent polymeric compound has a higher water absorption capacity for aqueous liquids with high ion concentrations than ionic ones, it is possible to stably retain a large amount of water in preparations with high ion concentrations (e.g., gel-type cosmetics, pharmaceuticals, poultices, etc.). Examples of nonionic water-absorbent polymeric compounds include modified polyalkylene oxides, N-vinylacetamide crosslinkers, and acrylamide crosslinkers.

[0033] More specifically, examples of such water-insoluble nonionic highly absorbent polymer compounds include commercially available products such as Sanwet IM-1000 (Sanyo Chemical Industries, water absorption capacity 800 times), Sunfresh AT-35 (Sanyo Chemical Industries, water absorption capacity 800 times), Aquacaulk (Sumitomo Seikagaku, water absorption capacity 30 times), and Aqualic CA (Nippon Shokubai, water absorption capacity 400 times).

[0034] When a water-insoluble nonionic highly water-absorbent polymer compound is blended, the amount thereof is preferably 0.1 to 30% by mass, more preferably 0.5 to 15% by mass, in the hydrogel.

[0035] As the polyhydric alcohol, for example, one or more of glycerin, sorbitol, ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, 1,3-butylene glycol, 1,3-propanediol, 1,4-butanediol, maltitol, xylitol, etc. can be used. When a polyhydric alcohol is blended, its amount is preferably 50% by mass or less in the hydrogel, more preferably 0 to 20% by mass. If the blending amount of the polyhydric alcohol exceeds 50% by mass, the cohesive force of the aqueous adhesive base decreases, and the aqueous adhesive base may remain on the adherend when peeled off.

[0036] Examples of oils include vegetable oils such as castor oil, olive oil, cacao oil, palm oil, camellia oil, coconut oil, wood wax, jojoba oil, grapeseed oil, and avocado oil; animal oils such as mink oil and egg yolk oil; waxes such as beeswax, whale wax, lanolin, carnauba wax, and candelilla wax; hydrocarbons such as liquid paraffin, squalane, microcrystalline wax, ceresin wax, paraffin wax, and petrolatum; natural and synthetic fatty acids such as lauric acid, myristic acid, stearic acid, oleic acid, isostearic acid, and behenic acid; natural and synthetic higher alcohols such as cetanol, stearyl alcohol, hexyldecanol, octyldodecanol, and lauryl alcohol; and esters such as isopropyl myristate, isopropyl palmitate, octyldodecyl myristate, octyldodecyl oleate, and cholesterol oleate.

[0037] The coloring matter is not particularly limited, and can be appropriately selected from those conventionally used in adhesive layers (plaster bodies) according to the purpose. Specific examples of the coloring matter include Red No. 2, Red No. 3, Red No. 102, Red No. 104, Red No. 105, Red No. 106, Red No. 201, Red No. 202, Red No. 203, Red No. 204, Red No. 205, Red No. 206, Red No. 207, Red No. 208, Red No. 213, Red No. 214, Red No. 215, Red No. 218, Red No. 219, Red No. 220, and Red No. 221. , Red 223, Red 225, Red 226, Red 227, Red 228, Red 230(1), Red 230(2), Red 231, Red 232, Red 401, Red 404, Red 405, Red 501, Red 502, Red 503, Red 504, Red 505, Red 506, Yellow 4, Yellow 5, Yellow 201, Yellow Color No. 202(1), Yellow No. 202(2), Yellow No. 203, Yellow No. 204, Yellow No. 205, Yellow No. 401, Yellow No. 402, Yellow No. 403(1), Yellow No. 404, Yellow No. 405, Yellow No. 406, Yellow No. 407, Green No. 3, Green No. 201, Green No. 202, Green No. 204, Green No. 205, Green No. 401, Green No. 402, Blue No. 1, Blue No. 2, Blue Examples of the pigments include color No. 201, blue No. 202, blue No. 203, blue No. 204, blue No. 205, blue No. 401, blue No. 403, blue No. 404, orange No. 201, orange No. 203, orange No. 204, orange No. 205, orange No. 206, orange No. 207, orange No. 401, orange No. 402, orange No. 403, brown No. 201, purple No. 201, purple No. 401, and black No. 401. When the pigment is added, the amount is preferably 0.00005 to 0.1% by mass in the hydrogel, and more preferably 0.0001 to 0.01% by mass. If the amount is too small, the effect of the addition may not be sufficient, and if the amount is too large, the color tone may become too strong. When a pigment is blended, it is preferable to dissolve the pigment in water, oil, alcohol, or the like and then knead it with other components so that uneven shading or spots of the pigment do not occur when the hydrogel is spread on the surface of the support.

[0038] Examples of moisturizing agents include polyhydric alcohols such as glycerin, propylene glycol, 1,3-butylene glycol, sorbitol, polyglycerin, polyethylene glycol, and dipropylene glycol; NMF components such as amino acids and sodium pyrrolidone carboxylate; and water-soluble polymeric substances such as hyaluronic acid, collagen, mucopolysaccharides, and chondroitin sulfate.

[0039] Examples of the antioxidant include dibutylhydroxytoluene, butylhydroxyanisole, ascorbic acid and its salts.

[0040] Examples of ultraviolet absorbing / scattering agents include 2-hydroxy-4-methoxybenzophenone, octyl dimethyl paraaminobenzoate, ethylhexyl paramethoxycyanamate, titanium oxide, kaolin, and talc.

[0041] Examples of preservatives include parabens such as methylparaben, propylparaben, and butylparaben; quaternary cations such as benzalkonium chloride and benzethonium chloride; sorbic acid; and benzoic acid.

[0042] The active ingredient is not particularly limited, and any active ingredient used in ordinary patches can be used. Specifically, the following can be used: [Non-steroidal anti-inflammatory agents] Examples of the antiseptic agent include salicylic acid and its salts, salicylic acid derivatives such as aspirin, acetaminophen, aminopyrine, antipyrine, oxyphenbutazone, sulpyrine, indomethacin, diclofenac sodium, ibuprofen, sulindac, naproxen, ketoprofen, etofenamate, salicylamide, triethanolamine salicylate, flufenamic acid and its salts and derivatives, meclofenamic acid and its salts and derivatives, colchicine, bufexamac, ibufenac, loxoprofen, fenbufen, diflunisal, alclofenac, phenylbutazone, mefenamic acid and its salts and derivatives, fenoprofen, bendazac, piroxicam, flurbiprofen, zaltoprofen, and etodolac. [Steroidal anti-inflammatory agents] Examples of such agents include amcinoid, prednisolone valerate, diflucortolone valerate, betamethasone valerate, betamethasone acetate, dexamethasone acetate, betamethasone dipropionate, dexamethasone, triamcinolone acetonide, lysinonide, hydrocortisone, flumethasone pivalate, fluocinonide, fluocinolone acetonide, fluotometholone, fludroxycortide, prednisolone, clobetasol propionate, beclomethasone propionate, betamethasone, methylprednisolone, methylprednisolone acetate, and hydrocortisone butyrate. [Muscle relaxants] Examples include diazepam. [Antiemetics] Examples include chlorpromazine. [Therapeutic agent for psoriasis] Methoxsalen and the like. [Skin softeners or emollients] Examples include hydroquinone, urea, heparin, and chondroitin sulfate. [Other medicinal ingredients] Examples of the active ingredient include indomethacin, glycol salicylate, methyl salicylate, ketoprofen, flurbiprofen, ibuprofen, suprofen, loxoprofen, zaltoprofen, piroxicam, felbinac, diphenhydramine, dibucaine, procaine, lidocaine, vitamin E derivatives, glycyrrhetinic acid, and derivatives thereof, and these can be used alone or in appropriate combination of two or more types. [Enzyme preparations] Examples of such enzymes include trypsin, papain, protease, lysozyme, streptokinase, plasmin, urokinase, hyaluronidase, α-chymotrypsin, serratiopeptidase, bromelain, and semi-alkaline peptidase. [Refreshing agent] Examples of such menthol derivatives include camphor, thymol, borneol, menthol, N-ethyl-p-menthane-carboxamide, p-menthane-3,8-diol, l-isopulegol, and l-menthyl glyceryl ether, as well as mint, peppermint oil, and spilanthol. [Vitamins] These include pantothenic acid, panthenol, vitamin A (retinol palmitate, etc.), vitamin E (d-α-tocopherol acetate), vitamin K, vitamin C, B vitamins, vitamin F, vitamin P, etc. [Warming agent] Examples include capsaicin, nonylic acid vanillyl amide, and nonylic acid vanillyl ether. [Herbal medicines] Powdered herbs such as oak leaf extract, soft herb extracts such as chili pepper extract, dried oak leaf extract, etc. Examples of such herbal extracts include dried medicinal extracts, herbal fluid extracts such as Swertia japonica fluid extract, and herbal tinctures such as Arnica tincture. [Plant extract] Examples of essential oils or extracts include anise, angelica, benzoin, immortelle, chamomile, garlic, cardamom, galbanum, caraway, carrot seed, guaiacwood, grapefruit, cypress, sandalwood, cedarwood, juniper, star anise, sage, geranium, celery, thyme, tarragon, turpentine, spruce, frankincense, violet, pine, parsley, birch, patchouli, hyssop, fennel, black pepper, linden flower, myrrh, marigold, lavender, yarrow, lemon, lemongrass, rose, rosemary, laurel, meadowsweet, peach, cornflower, eucalyptus, yuzu, and lavender. [Seaweed extract] Examples of such seaweed include extracts of seaweed belonging to the families Ulvaceae, Gracilariae, Gelidaceae, Mirranae, Laminariae, Wacaceae, Sargassaceae, Fucalaceae, Fonoriaceae, Azollaceae, Milletaceae, Bangiocarpaceae, Gigarinaceae, Porphyrae, Porphyrae, Chondrusaceae, Mozukuaceae, Durvillaiaceae, Lessoniaceae, and Dulcis, and among these, extracts of seaweed belonging to the family Durvillaiaceae are preferred.

[0043] When the above-mentioned active ingredient is blended in the hydrogel of the present invention, if the substance is listed in the Japanese Pharmacopoeia or the appropriate amount for use is specified in other documents, etc., it is preferable to blend it in accordance with the appropriate amount for use. In particular, the blending amount of a substance for which the appropriate amount for use is not specified is preferably about 0.0001 to 10 mass%.

[0044] As the flavor, natural plant flavors, blended flavor ingredients, synthetic flavor ingredients, etc. can be used, and these can be combined in any manner to mask the odor of the base or the drug, or to impart a flavor. Examples of the natural vegetable fragrances include fennel oil, castor oil, peppermint oil, peppermint oil, star anise oil, cinnamon oil, clove oil, thyme oil, turpentine oil, chenopodium oil, Japanese ginseng oil, eucalyptus oil, lavender oil, lemon oil, orange oil, touca oil, bergamot oil, rose oil, citronella oil, lemongrass oil, camphor oil, and geranium oil. Suitable examples of the blended fragrance components include limonene, terpinolene, camphene, citronellol, geraniol, nerol, linalool, menthol, borneol, terpineol, citronellal, citral, menthone, carbomenthone, camphor, citronellic acid, cineol, curcumene, farnesol, nerolidol, hinoki acid, and santalic acid. Other synthetic fragrance components that can be used include those described in "Synthetic Fragrances: Chemistry and Product Knowledge" by Genichi Indo, published by The Chemical Daily in 1996, and "Perfume and Flavor Chemicals" by Stephen Arctander, published in Montclair, NJ in 1969.

[0045] II. Support The support is not particularly limited and can be any of those used in the support layer of a normal patch. Examples of such materials include paper, thick weave, yarn weave, gauze, corduroy, flannel, and other woven fabrics, knitted fabrics made by flat knitting, rib knitting, tuck knitting, double knitting, and other manufacturing methods, nonwoven fabrics made by spunlace, spunbond, thermal bond, chemical bond, needle punch, and other manufacturing methods, knits, plastic films, plastic film / fiber laminated sheets, or plastic film / hydrophilic resin laminated sheets. In particular, knitted fabrics can follow the movement of the skin and are less likely to peel off. The thickness of the plastic film is not particularly limited and is usually about 5 to 100 μm.

[0046] Examples of materials include polyester fibers, polyethylene fibers, polyamide fibers, polyurethane fibers, rayon, hemp, etc. When a plastic film is used, materials such as polyethylene, polypropylene, polyethylene terephthalate, polyester, nylon, polyurethane, etc. can be used.

[0047] The weight of the support is 80g / m2 to prevent back staining. 2More than 200 g / m is preferable. 2 The following is preferable: 90 to 180 g / m 2 is more preferred.

[0048] The patch of the present invention can be widely used for the face, body, feet, etc., and can also be used on dry, cracked, rough skin (heels, etc.) In one embodiment of the present invention, the support of the paste layer further comprises a release liner on the reverse side of the surface that contacts the base fabric, and the patch of this embodiment is laminated in the order of the support (base fabric), the hydrous gel layer, and the release liner.

[0049] [Manufacturing method] The method for producing the patch of the present invention is not particularly limited, and any known method can be used; for example, the above-mentioned (A) to (C) components, water, and any optional components are mixed to obtain a hydrogel, and the obtained hydrogel is sandwiched between a support and, if necessary, a plastic film using a roll, and then pressed with a pressure roll, and a portion of the paste layer surface is removed, and the resulting product is cut into a predetermined shape using a score knife and a guillotine cutter. EXAMPLES

[0050] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following examples, unless otherwise specified, "%" in the composition indicates mass % and the ratio indicates mass ratio. It should be noted that Example 4 is a reference example.

[0051] [Examples and Comparative Examples] According to the composition shown in Table 1, water-soluble components other than the polymer compound were added to purified water with stirring to prepare pre-dissolved material 1. A lipophilic component was dissolved in polysorbate 80 to prepare pre-dissolved solution 2. The pigment was dispersed in glycerin to prepare a pigment pellet. Furthermore, powdered sodium carboxymethylcellulose and partially neutralized polyacrylic acid were added to glycerin and stirred (with a hand mixer at 2,000 to 3,000 rpm for 5 minutes) to uniformly disperse and dissolve them, thereby preparing preliminary dispersion 1. Next, the pre-dissolved material 2, small pigment particles, purified water, and optionally a polyalkylene oxide water-absorbing resin were added to the pre-dissolved material 1, and the mixture was stirred (at 300 rpm for 2 minutes using a Henschel mixer) to obtain a kneaded material 1. To this kneaded material 1, preliminary dispersion 1, polyacrylic acid, and purified water were added, and the mixture was stirred (at 300 rpm with a Henschel mixer for about 2 minutes) to obtain kneaded material 2. Furthermore, powdered dihydroxyaluminum aminoacetate and synthetic hydrotalcite were added to glycerin and uniformly dispersed therein to prepare preliminary dispersion 2. Preliminary Dispersion 2 was added to Kneaded Product 2 and stirred (at 300 rpm for about 2 minutes with a Henschel mixer) to obtain a water-containing pressure-sensitive adhesive composition. The obtained aqueous adhesive composition was spread to a predetermined amount by sandwiching it between a support and a liner film to form an aqueous adhesive layer (paste body) on the support, and then cut to a predetermined size. The obtained patch was wrapped in an inner bag (paper 64 g / m2) to prevent drying. 2 / PE15μm / AL7μm / EMAA20μm) and then sealed by heat sealing. The obtained patches were subjected to the following evaluations, and the results are shown in the table.

[0052] [Prevents back staining] Immediately after spreading, a stainless steel plate of the same size as the preparation and weighing 250g was placed on the release film side of the patch, and the patch was left to stand at 25°C for 12 hours or more while blocking the outside air. After standing, the stainless steel plate was removed, and the patch was placed on plain paper fixed to the stainless steel plate so that the support touched the plain paper, and gradually tilted. The tilt angle at which the patch slid off was measured and recorded as the back dye inhibition effect. The results are shown according to the following evaluation criteria. <Evaluation criteria> ◎: Sliding angle is less than 40 degrees ○: Sliding angle is 40 degrees or more and less than 60 degrees ×: Sliding angle is 60 degrees or more

[0053] [Shape retention] Nine healthy panelists applied the patch to the back of their hands, and after 20 minutes they removed it, evaluating the percentage of hydrous gel remaining on the skin. The average value was calculated and rated according to the following criteria. <Evaluation criteria> ◎: Water-containing gel remaining is 0 to less than 10% ○: Hydrogel remaining is 10% or more but less than 30% ×: Remaining hydrous gel is 30% or more (100%)

[0054] [Quickness of cooling sensation] Five healthy panelists applied the patch to the calf, and after five minutes, they performed a sensory evaluation of the cooling sensation according to the following criteria, and calculated the average score. A score of 4 or more was considered a pass. <Standards> 5: Feels very refreshing 4: Feels very refreshing 3: Feels a little cool 2: Feels slightly cool 1: Feels slightly cool 0: No cooling sensation

[0055] [Adhesive strength] The ball rolling device used in JIS Z 0237 was used, with an inclination angle of 30°, a run-up length of 100 mm, and a measuring surface of 50 mm. The ball sizes of the material specified in JIS G 4805 were 31 in total, ranging from 1 / 16 to 1 of the "ball size" of JIS B 1501, and the value 32 times the "ball size" was called the ball number, which was used as an index of adhesive strength. The test pieces were attached with the adhesive side facing up at a specified position on the inclined plate of the ball rolling device, and balls of each size were set in the gate. The gate was opened slowly, and the balls were rolled. The largest ball that completely stopped (the ball did not move for more than 5 seconds) within the measuring area was found, and the ball number at that time was used as an index of adhesive strength. A ball tack value of 20 or more was considered to pass.

[0056] [Table 1]

[0057] A hydrogel having the following formulation was prepared in the same manner as in the above-mentioned Example to obtain a patch, and the same effects as in the Example were confirmed. [Table 2]

[0058] The raw materials used in the above examples are shown below. Unless otherwise specified, the amounts of each component in the table are calculated as pure amounts. Polyacrylic acid 1: Toa Gosei Co., Ltd., "Jurimer AC-10H", weight average molecular weight: 150,000, neutralization degree: 0 mol% Polyacrylic acid 2: "Jurimer SH8" manufactured by Toagosei Co., Ltd., weight average molecular weight: 1 million, neutralization degree: 0 mol% Partially neutralized polyacrylic acid: "Aronvis AH-106X" manufactured by Toa Gosei Co., Ltd., weight average molecular weight: 4.5 million, neutralization degree: 40 mol% Sodium polyacrylate: "Aronvis SX" manufactured by Toagosei Co., Ltd., weight average molecular weight: 4.5 million, neutralization degree: 100 mol% Modified polyalkylene oxide water-absorbent resin: "Aquacaulk TWB-P" manufactured by Sumitomo Seika Chemicals Co., Ltd. Glycerin: "Japanese Pharmacopoeia Concentrated Glycerin" manufactured by Sakamoto Pharmaceutical Co., Ltd. Sodium carboxymethylcellulose A: Daicel FineChem Co., Ltd., "CMC1380", viscosity of 1% by mass aqueous solution: 1,524 mPa·s, viscosity of 5% by mass aqueous solution: 952 Pa·s, viscosity ratio 625 Sodium carboxymethylcellulose B: Daicel FineChem Co., Ltd., "CMC1390", viscosity of 1% by mass aqueous solution: 3,080 mPa·s, viscosity of 5% by mass aqueous solution: 1,400 Pa·s, viscosity ratio 466 Dihydroxyaluminum aminoacetate: "Glycinal" manufactured by Kyowa Chemical Industry Co., Ltd. Synthetic hydrotalcite: "Alcamac SH" manufactured by Kyowa Chemical Industry Co., Ltd. Sodium metaphosphate: "Sodium metaphosphate" manufactured by Taihei Chemical Co., Ltd. Disodium edetate: "Sodium edetate" manufactured by Chubu Cherest Co., Ltd. Methyl parahydroxybenzoate: Ueno Pharmaceutical Co., Ltd., "Methyl parahydroxybenzoate" Propyl parahydroxybenzoate: Ueno Pharmaceutical Co., Ltd., "Propyl parahydroxybenzoate" Polysorbate 80: Nikko Chemicals Co., Ltd., "TO-10MV" Tartaric acid: "Tartaric acid" manufactured by Iwata Chemical Industry Co., Ltd. l-Menthol: "l-Menthol" manufactured by Takasago International Corporation Peppermint oil: "Peppermint oil" manufactured by Takasago International Corporation Lavender oil: Takasago International Corporation, "Lavender oil" Eucalyptus oil: "Eucalyptus oil" manufactured by Takasago International Corporation Orange oil: "Orange oil" manufactured by Takasago International Corporation Lemon oil: "Lemon oil" manufactured by Takasago International Corporation Rosemary oil: "Rosemary oil" manufactured by Takasago International Corporation Sage oil: "Sage oil" manufactured by Vemanfis Fragrances Co., Ltd. Castor oil: "Castor oil" manufactured by Kosaka Pharmaceutical Co., Ltd. Red No. 226: "Red No. 226" manufactured by Hijimi Kasei Co., Ltd. Purified water: "Purified water (distilled)" manufactured by Kyoei Pharmaceutical Co., Ltd.

Claims

1. A patch comprising a hydrogel and a support, The hydrogel is A hydrogel obtained by crosslinking (A) one or more selected from polyacrylic acid and its salts with (B) a crosslinking agent, and further comprising (C) one or more selected from carboxymethylcellulose and its salts, The content of the component (A) in the hydrogel is 1 to 15% by mass, The content of the component (C) in the hydrogel is 1 to 8% by mass, the molar ratio of magnesium ions to aluminum ions in the crosslinking agent (magnesium ions / aluminum ions) is 2.0 to 2.5; A patch, in which the water content is 69 to 80% by mass in the hydrous gel.

2. The patch according to claim 1, wherein the content of the (B) component in the hydrous gel is 0.27 to 0.48 mass%.

3. 3. The patch according to claim 1, wherein the backing is a knitted fabric.

Citation Information

Patent Citations

  • Stretchable cataplasm

    JP1991161431A

  • Tacky adhesive composition and poultice

    JP1998265373A

  • Plaster

    JP2003095929A

  • Cataplasm and method for producing the same

    JP2004231567A